2003
DOI: 10.3171/jns.2003.98.4.0751
|View full text |Cite
|
Sign up to set email alerts
|

Long-term seizure outcomes following amygdalohippocampectomy

Abstract: The authors conclude that SelAH is a safe and effective surgical procedure for MTLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
154
0
16

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(174 citation statements)
references
References 30 publications
4
154
0
16
Order By: Relevance
“…Up to one-third of TLE patients have intractable, or drug-resistant epilepsy, and in these patients surgical treatment by anterior temporal lobectomy (ATL), which involves resection of both the neocortex and mesial structures (Engel et al, 1992), or a selective amygdalohippocampectomy (SAH), which involves resection of just the mesial structures (Wieser et al, 2003), is the standard of care. A randomized controlled trial has shown that the more commonly performed surgical treatment, ATL, significantly improves seizure-freedom and quality of life versus prolonged medical therapy with close to two thirds of patients being free of seizures at one year (Wiebe et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Up to one-third of TLE patients have intractable, or drug-resistant epilepsy, and in these patients surgical treatment by anterior temporal lobectomy (ATL), which involves resection of both the neocortex and mesial structures (Engel et al, 1992), or a selective amygdalohippocampectomy (SAH), which involves resection of just the mesial structures (Wieser et al, 2003), is the standard of care. A randomized controlled trial has shown that the more commonly performed surgical treatment, ATL, significantly improves seizure-freedom and quality of life versus prolonged medical therapy with close to two thirds of patients being free of seizures at one year (Wiebe et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Medical treatment failures are common, whereas surgery results in seizure control rates of up to 70%-90%. 26,54 Nevertheless, some patients do not have a significant improvement of their condition with surgery, even with complete resection of the suspected epileptogenic zone. Clinical factors such as seizure frequency, duration of epilepsy, sex, age of onset, and laterality of seizure focus have not been shown to Other authors have identified frequent secondarily generalized seizures, 18,20 history of encephalitis, 41 and head trauma 41,50 as poor predictive factors for good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…They were examined at the in-and outclinic between 1987 and 2000, and were followed-up for mean 4.5 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The schemes of diagnostic criteria (inclusion to an epileptic syndrome and criteria of exclusion from one) were worked up according to ILAE (1989) and Proposed Diagnostic Scheme for People with Epileptic Seizures and with Epilepsy (2001), and other published data.…”
Section: P782 Syndromic Classification In Childhood-onset Epilepsymentioning
confidence: 99%